Diversity of polypetalae plants in the Bodamalai Hills of Eastern Ghats, Tamil Nadu, India - Nigesh, S.; Vijayakumar, K. K. (Current Botany, 2025)
The diversity of polypetalae plants was studied in the Bodamalai Hills of the Eastern Ghats, Tamil Nadu, India. The results of the present study revealed that a total of 139 polypetalae plants from 41 families and 103 genera were documented in the current floristic exploration from the Bodamalai Hills. The dominant family in the study area is Fabaceae with 19 species, followed by Malvaceae (14), Rutaceae (11), Caesalpiniaceae (10), Mimosaceae (9), Combretaceae (5 species), Anacardiaceae, Apiaceae, Cleomaceae, and Rhamnaceae (4 each), Cactaceae, Capparidaceae, Meliaceae, and Menispermaceae (3 each), Burseraceae, Celastraceae, Molluginaceae, Myrtaceae, Passifloraceae, and Sterculiaceae (2 each), and other families with only one. The highest number of species was found in the genus Cassia (7), followed by Acacia (5), Sida and Ziziphus (4 each), Terminalia, Citrus, Cleome, Desmodium, and Cissus (3 each), Cassine, Capparis, Indigofera, Mollugo, and Syzygium (2 each), and the remaining 89 genera (1 each). The findings of this study revealed the diversity and significance of the polypetalae plants in the Bodamalai Hills for the native population’s way of life. Furthermore, baseline data on plant checklists, polypetalae plant diversity status, and plant adaptation to the research area are provided by this study.